A Review of Evidence on Gender Equality, Women's Empowerment, and Food Systems - Njuki, Jemimah; Eissler, Sarah; Malapit, Hazel J.; Meinzen-Dick, Ruth S.; Bryan, Elizabeth; Quisumbing, Agnes R. (Springer, 2023)
Achieving gender equality and women’s empowerment in food systems can result in greater food security and better nutrition, as well as more just, resilient and sustainable food systems for all. This chapter uses a scoping review to assess the current evidence on pathways between gender equality, women’s empowerment and food systems. The chapter uses an adaptation of the food system framework to organize the evidence and identify where evidence is strong, and where gaps remain. Results show strong evidence on women’s differing access to resources, shaped and reinforced by contextual social gender norms, and on links between women’s empowerment and maternal education and important outcomes, such as nutrition and dietary diversity. However, evidence is limited on issues such as gender considerations in food systems for women in urban areas and in aquaculture value chains, best practices and effective pathways for engaging men in the process of women’s empowerment in food systems, and how to address issues related to migration, crises and indigenous food systems. While there are gender-informed evaluation studies examining the effectiveness of gender- and nutrition-sensitive agricultural programs, evidence indicating the long-term sustainability of such impacts remains limited. The chapter recommends key areas for investment: improving women’s leadership and decision-making in food systems, promoting equal and positive gender norms, improving access to resources, and building cross-contextual research evidence on gender and food systems.